1, 4‐Dioxane‐Tuned Catalyst‐Free Methylation of Amines by CO2 and NaBH4. Issue 14 (3rd July 2018) - Guo, Zhiqiang; Zhang, Bo; Wei, Xuehong; Xi, Chanjuan
Abstract: A catalyst‐free reductive functionalization of CO2 with amines and NaBH4 was developed. The N ‐methylation of amines was carried out with CO2 as a C1 building block and 1, 4‐dioxane as the solvent. Notably, the six‐electron reduction of CO2 to form the methyl group occurred simultaneously with formation of the C−N bond to give the N‐methylated amine. Abstract : C1, C−N them all : A catalyst‐free six‐electron reduction of CO2 to methyl with simultaneous formation of a C−N bond was attained by using NaBH4 as the reducing reagent in 1, 4‐dioxane, enabling the N ‐methylation of amines with CO2 as a C1 building block.